Meta-analysis to evaluate the effect of including molasses in the diet for dairy cows on performance, milk fat synthesis and milk fatty acid - Torres, Rodrigo de Nazaré Santos [UNESP]; Bertoco, Joao Pedro Amaral [UNESP]; de Arruda, Maria Carolina Gonçalves [UNESP]; Coelho, Larissa de Melo [UNESP]; Paschoaloto, Josimari Regina [UNESP]; Júnior, Gercílio Alves de Almeida; Ezequiel, Jane Maria Bertocco [UNESP]; Almeida, Marco Tulio Costa (Elsevier, 2021)
Different types of molasses have been included in diets for ruminant animals, mainly as a substitute for energetic ingredients, such as corn and sorghum. However, the positive effect of this inclusion on the performance, fatty acid profile and composition of cows’ milk is not yet clear. In this sense, this study aimed to evaluate by meta-analysis the effect of including molasses in diets for dairy cows on the milk fatty content and fatty acid in milk. The eleven peer-reviewed publications with 52 treatments means were included in data set. The effect of including molasses in the diet of dairy cows were evaluated using random effect models to examine the weighted mean differences (WMD) between molasses treatment (diets with molasses inclusion) and control treatment (without molasses inclusion in the diet). Heterogeneity was explored by meta-regression and subgroup analysis considering genetic group, days in milk, molasses in the diet (g/kg DM), type of molasses, concentrate in the diet (g/kg DM). The covariates genetic group and days in milk influenced most the variability of responses to the inclusion of molasses in the diet for dairy cows. Molasses supplementation to dairy cow diets negatively impacted animal performance and milk composition by reducing milk yield and milk protein, lactose yield and concentration (with inclusions levels of molasses greater than 60 g/kg of DM). However, inclusions of molasses up to 120 g/kg of DM in diet, did not affect the yield and concentration of fat in milk. The inclusions of molasses in the diet caused a reduction in the concentration of unsaturated fatty acids (Total UFA -10.67%); however, it increased the concentration of omega-3 fatty acids in milk (11.52%), without affecting total of polyunsaturated fatty acids and C18: 2 cis-9, trans-11 CLA.
Keywords: Co-product; Milk solids; Omega-3; Polyunsaturated fatty acid; Soluble carbohydrates